Not “Alona” monacantha Sars, 1901, but Coronatella hardingi (Brehm, 1957) Crustacea: Branchiopoda: Cladocera) in the Afrotropics - Damme, Kay Van (Zootaxa, 2016)
Many taxa formerly housed in the lump genus Alona Baird, 1843 remain data-deficient. These species are often overlooked or wrongly identified during faunistic and ecological studies. “Alona” hardingi (Brehm, 1957) is a lesser known taxon, hidden for decades under records of “Alona” monacantha Sars, 1901. Both taxa have recently been allocated to the genus Coronatella Dybowski & Grochowski, 1894, yet without revision of the former. The morphology of Coronatella hardingi (Brehm, 1957), a widespread and abundant species in Afrotropical freshwater habitats, is examined here for the first time, including the first description of the male. The species is redescribed, based on populations from Southern Africa and confirmed as a good species and a valid sibling of the Neotropical C. monacantha (Sars, 1901) and the SE Asian C. acuticostata (Sars, 1903). The study of the Afrotropical C. hardingi allows a better understanding of this small tropical species complex, for which a diagnosis is included.